SEASONAL CHANGES IN THE BIOCHEMICAL COMPOSITION OF A HILLSTREAM FISH GARRA MULLYA (SYKES) - Somvanshi, V S (Indian Journal of Fisheries, 2011)
In the hillstream fish Garra Mullya (Sykes) marked seasonal variations inphosphorus, water, fat, protein and glycogen were observed during a one-yearstudy. The fat and water contents were inversely related; maximum fat was observedduring the prespawning months, while the minimum after the breeding. Therelationship between fat and protein was a direct one. The muscle glycogen wasin assocation to feeding and spawning activity. High energy values were foundthroughout the prespawning period.